Directrices tecnicas para el movimiento seguro del germoplasma del cacao. Version revisada de las Directrices Tecnicas de FAO/IPGRI No. 20 (Tercera actualizacion, Octubre de 2017) - End, M.J.; Daymond, Andrew J.; Hadley, P.; Global Cacao Genetic Resources Network; Bioversity International (2017)
These guidelines describe technical procedures that minimize the risk of pest introductions with movement of cacao germplasm for research, crop improvement, plant breeding, exploration or conservation.